Horsing Around: Carnivalesque Humor and the Aesthetics of Dehierarchization in Mister Ed - Stefan L. Brandt (European Journal of American Studies)
This essay discusses the aesthetics of dehierachization in one of the pioneering sitcoms in American television—the CBS-produced Mister Ed (1961–1966). Drawing on the concepts of “the animal subaltern” (Willett), “bestial ambivalence” (Wells), and “liminal animal denizenship” (Donaldson and Kymlicka), I argue that the show constructs its protagonist, a talking horse named Mister Ed, as a shapeshifting character who humorously challenges established assumptions regarding the human/animal dichotomy. Designed as a sitcom, Mister Ed employs a technique that I describe, following Bakhtin, as “carnivalesque humor.” Within this aesthetic framework, the title character figures as an ambiguous and grotesque character who rejects social conventions and restrictions, oscillating between the position of a stand-in for humans and that of a liberated animal. Mister Ed playfully advocates a radical move toward alternative representations of body, identity, and species, even postulating an analogy between the African American Civil Rights Movement and the discourse of animal liberation. Following a long tradition in animal fiction, the show sets out to expose hierarchies and injustices in society by employing an animal as its chief focalizer. Conceived in this manner, Mister Ed challenges what Jacques Derrida has termed “the possibility of the impossible,” namely the notion that animals can never be endowed with a sense of subjectivity. In the comedic, fictional realm of the show, the “impossible” becomes a subversive reality. Mister Ed assumes the position of a powerful subject which is endowed with “non-human agency” (Armstrong). In this sense, Mister Ed creates a scenario in which the “absolutely marginal” (Berger), indeed, returns the viewers’ gaze, inviting them to share and valorize this outside perspective, if only for the duration of one twenty-five minute episode at a time.